الرقابة على الصفقات العمومية - قرقور سهام  بوزيدي زينب (المسيلة, 2023)
نظرا ألهمية أنواع عقود الصفقات العمومية، كونها أبرز المجاالت التي تتحرك فيها األموال العامة بسبب ارتباطها بخزينة الدولة، حيث تعد وسيلة ضرورية في تحقيق التنمية وتطوير السياسة االقتصادية واالجتماعية للدولة، فإن المشرع الج ازئري أحاطها من خالل المرسوم 15-247 بكافة الضمانات القانونية لضمان شفافيتها وفعاليتها في حسن استعمال المال العام وترشيد النفقات ، عن طريق تعزيز آليات رقابية صارمة، والتي تعددت أنواعها في مراقبة مدى التزام اإلدارة بالبنود المقررة قانونا، ومالزمة الصفقة العمومية في مختلف مراحلها قبل وبعد التنفيذ، من أجل الوقاية من شتى أنواع جرائم الفساد بغية الحفاظ على الصالح العام . وبالرغم من أن المشرع ألم بجميع االحتياطات اآلزمة لحماية المال العام المتعلقة بالصفقات العمومية إال أنه لم يستطع سد كل الثغرات المتعلقة بجرائم الفساد على الصفقات العمومية. Summary In view of the importance of the types of public procurement contracts, being the most prominent areas in which public funds move because of their connection to the state treasury, as they are a necessary means in achieving development and developing the economic and social policy of the state, the Algerian legislator surrounded them through Decree 15-247 with all legal guarantees to ensure their transparency and effectiveness in the proper use of public money and the rationalization of expenditures, By strengthening strict control mechanisms, which are of various types in monitoring the extent of the administration’s commitment to the provisions stipulated by law, and accompanying the public deal in its various stages before and after implementation, in order to prevent various types of corruption crimes in order to preserve the public interest... Although the legislator was aware of all the necessary precautions to protect public funds related to public procurements, he was unable to bridge all the loopholes related to corruption crimes in public procurements.
Keywords: الرقابة - الصفقات العمومية